PTH-022 A Novel Experience of The Pillcam® ESO 3 Capsule Endoscope In Patients Unwilling To Undergo Conventional Upper GI Endoscopy. (17th August 2016) - Ching, H-L; Phillips, V; Healy, A; Sidhu, R; McAlindon, ME
Abstract : Introduction: Gastroscopy (OGD) is the gold standard test for investigating dyspepsia, but is uncomfortable, incurs the risk of intubation and sedation and has a diagnostic yield in our practice in 16.4% (data submitted). Capsule endoscopy is safe, non-invasive and well-tolerated. Furthermore, capsules to image the oesophagus are now used in routine clinical practice. We test the feasibility and safety of a novel protocol using the ESO3 upper gastrointestinal (GI) capsule (Given Imaging Ltd) which boasts an improved field of view and battery life compared to earlier models. Methods: All consecutive patients undergoing investigation with the ESO3, between December 2015 and February 2016, were prospectively recruited. All patients required upper GI investigation but had declined conventional OGD ± barium studies. Patients were asked to drink 1 L of water containing simethicone prior to the procedure. They were then asked to swallow the ESO3 and adopt lying positions in 3 different directions at 3 angles (30° head down/up and horizontal) for 3 minutes each. Data on patient demographics, procedural data and patient tolerance was reviewed. Results: 10 patients (mean age 49±17.3 years, 50% male) were included. Indications for the ESO3 included investigation for dyspepsia (n = 2), iron deficiency anaemia (n = 2), variceal screening (n = 3), suspected gastric Crohn's disease (n = 1), subjective dysphagia (n = 1) and assessment of oesophageal ulcer healing (n = 1). Pathologies detected at CE included oesophagitis (n = 2), hiatus hernias (n = 3), oesophageal ulcers and erosions (n = 3), oesophageal varices (n = 3) and gastric and Cameron ulcers (n = 1, each). The mean time of the ESO3 transit in the oesophagus, stomach and small bowel was 12±9 secs, 58±27 mins, 23±22 mins respectively. The mean reading time for the capsule video was faster with the accelerated reading mode (39±18.4 mins) than with standard mode (79±14.6 mins) using the RAPID® software (p < 0.05). Mean post-procedural anxiety, discomfort and pain scores were excellent (scores from worst-best =0-10; 0, 0.7, 0 respectively). Visualisation (grade from worst-best =1-5) of all areas of the upper GI tract was also excellent; oesophagus (5±0), gastric cardia (5±03), fundus (4±1.1), body (5±0.6), antrum (5±0.3) and the first and second part of the duodenum (both 5±0). Complete examination to D2 was achieved in 80%. No complications were seen. Conclusion: We report the first study of a novel protocol demonstrating the feasibility and safety of the ESO3. Further protocol amendments are necessary to improve reading time and visualisation while randomised control trials are needed to compare diagnostic yield to conventional OGD. However, the excellent patient tolerance affords an alternative upper GI investigative tool worth pursuing. Disclosure of Interest: None Declared